Technical study of digital display using Peripheral Interface Controller (PIC) microcontroller based system - Mohd Nasir, Haron; Uda, Hashim, Prof. Dr. (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology (MUCEET) 2009, 20th - 22nd June 2009 organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis at MS Garden Hotel, Kuantan, Pahang, Malaysia.